A PILOT STUDY ON SUN PROTECTION FACTOR OF PLANT EXTRACTS: AN OBSERVATIONAL STUDY - S, Priyanka; Rani Inala, Mary Shobha; Hs, Nandini; Avm, Kutty; P, Kiranmayee (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The aim of the present work is to investigate the presence of ultraviolet (UV) light absorption capacity of the selected plant extracts. Chemical-based sunscreens provide protection against the sun's rays, in particular, UV radiation. Sometimes, exposure to these chemicals leads to allergies to the skin. The best way to protect skin from chemical and photoallergies is to use plant-based creams and lotions. Methods: Methanol and water extracts of Datura metel leaves and flowers; Loranthus leaves and flowers; and Eucalyptus leaves were prepared and checked their UV absorption ability from 200 nm to 450 nm. Different concentrations of the same extracts were tested for their sun protection factor (SPF) using Mansur formula from 290 to 320 nm. All the extracts showed absorption at UV range. Result: The calculated values of SPF were fallen in the range of 0.4–23.5. Among the three plants used in this study, methanol extract of Eucalyptus showed highest UV absorption than the other two plants. In vitro studies of a few phenolics from various plants have been found to be mutagenic. This might be the result of pro-oxidant than antioxidant action of these compounds. Keeping in view of human use as SPFs, it is indispensable to investigate the toxic effects of the extracts. Conclusion: The preliminary findings of this study reveal that the methanol extract of Eucalyptus has a high sun protection effect. This extract can be used as additives in other sunscreen formulations to enhance their SPF.